Power and Phase Current Balancing Technique for Bidirectional Cascade Three-Phase CLLLC Resonant Converters - Prachaya Kowi; Sompob Polmai (My University, 2025)
This paper presents an interleaved configuration of bidirectional cascade three-phase CLLLC resonant converters (BCTRC) topology. The proposed approach reduces the high-voltage transformer turns ratio, minimizes input/output current ripple, and improves current sharing across MOSFETs and power balance among converters, thereby lowering device stress and extending the system's lifespan. In practice, component tolerances lead to resonant parameter mismatches, resulting in phase current imbalance and unequal high-side voltage sharing. To overcome this, a fundamental voltage control (FVC) method is employed for power balancing, while trigonometric current balancing (TCB) is used to equalize phase currents. Simulation results confirm that the combination of FVC and TCB achieves the lowest unbalanced coefficient (Uf) decreasing from 8.36% to 2.93% and reduces the power sharing error (PSE), decreasing from 9.78% to 0.24% in the forward case. In the reverse case Uf decreases from 9.37% to 1.62%, while PSE is reduced from 9.66% to 0.58%. Furthermore, the proposed method equalizes the high-side voltages and maintains zero voltage switching (ZVS) under both forward and reverse power flow conditions.
Keywords: Advanced DC-DC Converters; Advanced Power Amplifier Design; Multilevel Inverters and Converters